A dreadful splendor : a novel - Myers, B. R. (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"In this wickedly whimsical Gothic murder mystery brimming with romance, betrayals, and chills, a fake spiritualist is summoned to hold a séance for a bride who died on the eve before her wedding, but as nefarious secrets are revealed, the line between hoax and haunting blurs."--Amazon.com.